Analisis Biaya Promosi untuk Meningkatkan Pendapatan pada Djava Wedding Karawang - Desi Tri Wahyuni; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The costs incurred for promotional activities can increase revenue, because from this activity consumers can find out information about products or services sold by the company. The level of income that is predicted to increase along with the amount of costs incurred. Wedding organizer is a service that provides services to help the bride and groom in meeting their wedding needs according to the theme chosen by the bride and groom. The purpose of this research is to analyze the costs incurred for promotion, income earned as well as activities carried out to increase income at Djava Wedding Karawang. The population in this study data on the financial statements of Djava Wedding Karawang for 5 years, namely 2018 - 2022, so that the samples used are promotional costs and income. This research uses quantitative descriptive methods. The results of the research show that there is a promotional fee issued by the largest company at the Expo Wedding activity of Rp. 25.000.000 while the smallest in make-up model activities is Rp. 300.000. The income obtained by the company has fluctuated due to promotional activities carried out by Djava Wedding Karawang, namely through the Wedding Expo which can increase revenue by 11.11% worth Rp. 277.980.000 from promotional income and Rp. 13.899.000 from booking.